The people of Sparks / 2. - DuPrau, Jeanne (DuPrau, Jeanne. Ember., 2005)
Lina and Doon are thrilled to see their people join them above ground in the vibrant village of Sparks, but suspicion and prejudice soon turn the villagers and newcomers against each other.